Photography, Democracy and Injustice: the Image Regarding the Pain of the Other - Juan Albarrán Diego (FahrenHouse, 2009)
Since the birth of photography, the image has been used as a medium of con- trol, vigilance and repression. In this paper we review some of the last two centuries photogra- phical uses focusing three cases where the photography has played a fundamental role as a tool to purge responsibilities. We do a no-lineal survey relating the ways to produce images and the institutional fields where they are inscribed to get a paradoxical value of truth.